Способ для одновременного измерения температуры в режущем инструменте и заготовке при глубоком безвыводном сверлении отверстий в литейных алюминиях - Маршуба, Вячеслав Павлович; Дрожжин, В. И. (НТУ "ХПИ", 2003)
The method for definition of quantity at shearing and under deformation, processed material in spiral drill and work piece, is proposed. This method helps to register the indications of the thermocouples at deep drilling of casting aluminum on the vertical drilling machines. The results about advisable application of this method, measuring the temperature in dependence on quantity of the front and back angles of cutting tool, the depth of drilling and regimes of cutting are given.
Keywords: поле температурное; стружка; обработка механическая; резание; среда технологическая; среда смазочно-охлаждающая